Seed deposition patterns and the survival of seeds and seedlings of the palm Euterpe edulis - Pizo, M. A.; Simao, I (Elsevier B.V., 2001)
The seed deposition pattern created by a seed disperser is one of the components of the efficiency of a species as seed disperser, and ultimately may influence the recruitment of a plant species. In this study, we used the seeds of a bird-dispersed forest palm, Euterpe edulis, to investigate the effects of two distinct seed deposition patterns created by birds that defecate (clumped pattern) and regurgitate seeds (loose-clumped pattern) on the survival of seeds experimentally set in an E. edulis-rich site, and of seedlings grown under shade-house conditions. The study was conducted in the lowland forest of Parque Estadual Intervales, SE Brazil. Clumped and loose-clumped seeds were equally preyed upon by rodents and insects. Although clumped and isolated seedlings had the same root weight after 1 year, the isolated seedlings survived better and presented more developed shoots, suggesting intraspecific competition among clumped seedlings. Our results indicate that animals that deposit E. edulis seeds in faecal clumps (e.g. cracids, tapirs) are less efficient seed dispersers than those that regurgitate seeds individually (e.g. trogons, toucans). Intraspecific competition among seedlings growing from faecal clumps is a likely process preventing the occurrence of clumps of adult palms. (C) 2001 Editions scientifiques et medicales Elsevier SAS.
Keywords: Atlantic forest; Euterpe edulis; seed deposition pattern; seed dispersal; seed predation; seedlings